Evaluation of performance, diversity, and trait relationships of butterfly pea (Clitoria ternatea) genotypes M4 generations - TRY ZULCHI; ALI HUSNI; DWINITA W. UTAMI; REFLINUR REFLINUR; MIA KOSMIATIN; HARIS MAULANA; TARKUS SUGANDA; VERGEL CONCIBIDO; AGUNG KARUNIAWAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Zulchi T, Husni A, Utami DW, Reflinur, Kosmiatin M, Maulana H, Suganda T, Concibido V, Karuniawan A. 2024. Evaluation of performance, diversity, and trait relationships of butterfly pea (Clitoria ternatea) genotypes M4 generations. Biodiversitas 25: 3476-3485. Butterfly pea, a versatile forage plant with perennial growth and adaptability, is the focus of a crop improvement program aimed at enhancing production performance and nutritional contents through mutation polyploid induction. This study aimed to identify butterfly pea genotypes with higher agronomic values, genetic diversity, trait relationships, and traits-specific excellence. The mutants (M4) comprised 95 genotypes, and local varieties were used as controls. The experiments were conducted in an augmented design with local cultivars used as checks in Bogor, Indonesia, from March to August 2021. The results revealed that butterfly pea genotypes improved in stem diameter, fresh and dry weight biomass, and number of seeds per pod compared to local cultivars by 8.6%, 9.07%, 7.82%, and 5.37%, respectively. The nutritional content of protein, carbohydrates, and lipids was also enhanced. Additionally, early flowering times were detected for the butterfly pea genotypes. Further, principal component analysis indicated that the genetic diversity of butterfly pea mutants is broad, underscoring the richness of the research data. The four axes of the analysis had eigenvalues ranging from 2.573 to 1.129, with a cumulative value of 67.56% and a degree of variation contributed by dry-weight biomass. Genetically, butterfly pea genotypes can be categorized into four groups on genetic distance, with several variables displaying positive correlations. Butterfly pea genotypes such as BP78, BP70, BP58, and BP46 have been earmarked as genotypes possessing high biomass and good nutritional qualities. The butterfly pea genotypes in the current study have the potential to be selected for improvement or utilized as a parent in a hybridization program.